Implementasi Konsep Community Based Tourism Pada Daya Tarik Wisata Religi Pulau Mansiman Kabupaten Manokwari Provinsi Papua Barat - Wororik, John Richard; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2022)
This research was conduted to support the Indonesian government in declaring tourism as a leading sector in increasing the country’s foreign exchange. In addition, to explore and manage various tourism potentials in various regions in Indonesia, by determining the community as the main actor through community empowerment inn various tourism activities so that the maximum benefits of tourism are prioritised for community. This report is written with the aim of being to identify what factors are included in the application of the concept of communit based tourism to the religious tourism attraction of Mansinam Island is in accordance with the principles of the concept of communitybased tourism. The research method used in this research includes qualitative and quantitative data types, primary data sources and secondary data sources, data collection techniques, and data analysis techniques. The results of the discussion can be conclded that the implementation of the concept of communitybased tourism on the religious tourism attraction of Mansinam Island can develop better, despite the current development is still inssuficient. This is due to the lack of regional budgets; there is no good cooperation between the various parties involved and the limited knowledge of the community on better tourism development. The results of the study provide guidance on the implementation of the commumity based tourism concept on Mansinam Island namely by re-planning the development of tourism on Mansinam Island, the results of the planning will become a benchmark for the district government to request additional budget for tourism development on Mansinam Island. Local governments are olso expected to re-evaluate the Mansinam Island Management Isntitute, and providing training to local communities on tourism development in this island to better future. Keywords: Implementation, Community Based Tourism, Development